2014
DOI: 10.1103/physrevlett.113.033003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Hyperfine Quenching Rate of the Clock Transition in Yb171

Abstract: We report the first experimental determination of the hyperfine quenching rate of the 6s(2) (1)S(0)(F = 1/2) - 6s6p (3)P(0)(F = 1/2) transition in (171)Yb with nuclear spin I = 1/2. This rate determines the natural linewidth and the Rabi frequency of the clock transition of a Yb optical frequency standard. Our technique involves spectrally resolved fluorescence decay measurements of the lowest lying (3)P(0,1) levels of neutral Yb atoms embedded in a solid Ne matrix. The solid Ne provides a simple way to trap a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…13 The lifetimes of the Yb( 3 P 1 ) state in RG matrices have been recently measured by the Argonne group. 15 It was found that the Yb/Ar emission, averaged with the intensity profile over the 543-600 nm range, decays exponentially at a rate of 1.8 × 10 6 s −1 , close to the gas-phase value of 1.16 × 10 6 s −1 . 16 Moreover, attempts have been made to identify the emission from the metastable Yb 3 P 0 or 3 P 2 states.…”
Section: S 2 1 S 0 → 6s6p 1 P 1 Emission Spectramentioning
confidence: 71%
See 1 more Smart Citation
“…13 The lifetimes of the Yb( 3 P 1 ) state in RG matrices have been recently measured by the Argonne group. 15 It was found that the Yb/Ar emission, averaged with the intensity profile over the 543-600 nm range, decays exponentially at a rate of 1.8 × 10 6 s −1 , close to the gas-phase value of 1.16 × 10 6 s −1 . 16 Moreover, attempts have been made to identify the emission from the metastable Yb 3 P 0 or 3 P 2 states.…”
Section: S 2 1 S 0 → 6s6p 1 P 1 Emission Spectramentioning
confidence: 71%
“…39 This coupling has effectively been demonstrated for Yb through the measurements of the 3 P 1 and 3 P 0 lifetimes in the RGs. 15 We therefore take the populations n v , n b , and n r as proportional to the amplitudes of the 6s6p 3 P 1 violet, blue, and red emission peaks, respectively, further assuming that the overlap between each Gaussian peak is small.…”
Section: B Model Of Migrationmentioning
confidence: 99%
“…Studies of atomic species isolated in rare gas (RG) solids are of interest in many fundamental and applied respects. For atomic physics, they complement characterization of the interatomic interactions and electronic energy transfer pathways [1], can give atomic structure parameters unavailable from gas-phase experiments [2], and occasionally provide highly sensitive detection schemes [3]. For solid state physics and chemistry, they serve as the models of the structure, mobility and electronic properties of the point defects, as well as of the reactivity in solids [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the Ne crystal is a less perturbing envi-ronment than the heavier RGs. Isolated in it, the Yb electronic structure is still qualitatively the same as in vacuum, while the lifetimes of excited states are not significantly different [10,11]. Based on these observations, single atom detection of Yb in sNe would appear feasible, which could then be extended for use in detecting rare nuclear reactions [22].…”
Section: Introductionmentioning
confidence: 82%
“…Examples of systems studied specifically for these applications include alkali atoms in both solid RGs [8] and parahydrogen [9], Yb atoms in solid Ne [10,11] and Tm atoms in solid Ar and Kr [12]. For these species, medium effects generally broaden linewidths and shift transition frequencies by several hundred wavenumbers [8].…”
Section: Introductionmentioning
confidence: 99%